A study of the structural changes in a chitosan matrix produced by the adsorption of copper and chromium ions - Anbinder, Pablo Sebastián (2019)
A study of the structural changes at micro- and nano-scale in a chitosan matrix after the adsorption of different metal ions is presented. Toward this aim, samples of chitosan films soaked in different concentrations of copper(II) and chromium(VI) aqueous solutions were prepared. Cu and Cr ions were selected as sorbates since they have different ionic properties. The effect of the adsorbed metal ions on the microstructure of the chitosan matrices were studied using Fourier transformed infrared spectroscopy, UV?vis spectroscopy, differential scanning calorimetry and thermogravimetric analysis. To go further into the study of the samples at the molecular level, the nuclear technique positron annihilation lifetime spectroscopy was used. Results are discussed in terms of the interaction between the metal ions and the chitosan functional groups.ChitosanPositron annihilation spectroscopyHeavy metal adsorptionStructural properties